Comparison of banking stock price movements using KNN and Linier Regresi methods - Wresti Andriani; Gunawan; Sawavyya Anandianskha (Jurnal Mantik, 2023)
Stock price movements are a reflection of various situations and factors such as economics, politics and markets. Influencing factors such as economic news both foreign and domestic such as monetary policy, changes in interest rates and political events such as general elections. Indonesian politics is currently holding a general election process, the Presidential election can influence stock movements. Causing investors to be more careful about investing in this case in banks in Indonesia that have state-owned status, such as BTN, BRI, BNI and Bank Mandiri. This research predicts stock price movements using the Linear Regression method compared to the k-NN method, to find the best evaluation results from the two methods in selecting banks that are more profitable and do not influence political process factors. The results obtained were that Bank Mandiri was safer and promised profits using the Linear Regression method which was better than k-NN with RMSE 281,012, MAE 97,909 and MSE 80348,873. Bank Mandiri is safer and promises profits